PENGARUH IKLAN HIJAU PADA SIKAP DAN PILIHAN TEMA PADA IKLAN HIJAU - PRAM SURYANADI (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2019)
The purpose of this study is to analyze whether there are differences in attitudes towards green advertising between high-involvement consumers and low-involvement consumers and to compare consumer cognitive responses and consumer affective responses to advertising and to examine the importance of certain themes that have high involvement and consumer consideration. with low involvement. The themes presented include corporate image, environmental labels, and product recycling symbols.This study shows that there is a difference between high-involvement consumers and low-involvement consumers in terms of their attitudes towards green advertising across all measures of perception of green advertising. The findings provide practitioners with a useful vision of the types of themes consumers prefer for green advertising Keyword : Green Products, Green Advertising, Environtmental label, Consumer involvement.